Performance improvement through value stream mapping – a manufacturing case study - Bugvi, Salman Abubakar; Hameed, Khurram; Jamil, M. Fawad; Irfan, Ali; Murtaza, Shahid; Qaiser, Muhammad; Bilal, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2021)
The successfulness of Value Stream Mapping (VSM) as a tool for taking a snapshot of the production flow efficiency is well established. The development of a large-scale visual map of processes and their interactions is beneficial for problem analysis and subsequent solution. Through VSM, managers gain a deeper understanding of the organization processes carried out in coordination with people in a system approach. A case study was conducted at a Small and Medium Enterprise (SME) in Pakistan which manufactures ceiling fan winding machines. The aim of this study was to explore the possibilities of shortening the lead-time, waste and highlight important strategies, steps which could be undertaken by management for improvement in productivity, cost and quality. The study maps the organization systematically through the use of VSM. The Lean Implementation Techniques (LIT) steps were followed with identification of value stream process, lean metrics, mapping of current state and proposing an improved future state value stream map. The intervention suggested is layout modification by reducing 7 stations to 6 stations and streamlining the operations. The layout modification results in lower defects, controlling overproduction, managing inventory buffers from a linear approach to an optimized level. This also resulted in reduction of processing time of each unit by around 19 % and the production lead time of 100 units by around 21%. This study through VSM proposes improvement by enforcing pull system, supplier relations, modifying layout and production processes, Just in Time (JIT) delivery of materials and parts, scheduling transport resources efficiently and reducing inventory buffers.